Numerical Study of Sodium Bicarbonate Production in Industrial Bubble Columns - Jasim Humadi; Ekehwanh Rasheed (Journal of Chemical and Petroleum Engineering)
The purpose of this study is to explore the physio-chemical factors that affect sodium bicarbonate synthesis in industrial bubble columns employing CFD simulations. The model represents gas-liquid-solid systems and introduces turbulent phenomena and chemical reactions into the model. Parameter optimizations are performed to analyze the operational parameters such as gas flow rate, liquid phase characteristics, column geometry, and reaction kinetics. This study demonstrates a better understanding of the optimal reaction conditions for maximum NaHCO3 yielding, fast enough kinetic reaction, and less undesired byproduct formation, as well as introducing productive and environmentally friendly approaches to synthesizing chemical products. The broader width of the column increases turbulent mass diffusivity, but decreases turbulent viscosity. With a broader column width, column pH gradient decreases, due to the increased liquid amount. The concentration of the solutions falls, as the width of the column decreases. For the height of 107 mm, the concentration is 95 mmol/L; this value is 82 mmol/L for the height of 200 mm. Supersaturation increases with column height. For a height of 200 mm, the supersaturation is equal to 0.015. The molar proportion of carbon dioxide in gas is a function of column height, thus 35% at 200 mm and 20% at the air end.